Analisis Kemampuan Kolam Retensi Brimob di Jalan Demang Lebar Daun Sebagai Tampungan Pengendali Banjir - Kurnia, Dwi; Syarifudin, Achmad; Mulyati, Ely; Prawira, Wanda Yudha (Universitas Sulawesi Tenggara, 2025)
The Mobile Brigade (Brimob) retention pond is located on Jalan Demang Lebar Daun, Ilir Barat 2 District, Palembang City. The retention pond is in poor condition. It covers 2,147.6 m2 and has a depth of 3 meters. The area of the Brimob retention pond often overflows during heavy rainfall and floods the surrounding roads.From the discussion and calculations, the analysis of the Brimob retention pond shows that the inlet discharge is 6.039 m3/sec. The total flood discharge is 2.1609 m3 for the Brimob retention pond area. The capacity of the Brimob retention pond is 73119m3. From the points above, based on the objectives of this analysis, it is concluded that the retention pond capacity is 73119 m3.